2014
DOI: 10.1038/hr.2014.100
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability of urinary salt excretion and blood pressure in hypertensive patients

Abstract: We investigated the long-term trend and variability of urinary salt (sodium chloride) excretion in hypertensive patients. Subjects included 186 hypertensive patients (103 women and 83 men, mean age: 58.5±10.5 years) who underwent 10 successful 24-h home urine collections over a mean observation period of 7.7 years. We measured 24-h urinary salt excretion and blood pressure (BP) sequentially at the time of each collection and monitored the long-term trend and variability of urinary salt excretion. BP significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Accurately assessing individual salt intake requires several days of complete 24‐hour urine collections while our criteria only required a single 24‐hour period to assess salt intake. Accurate assessment of salt intake relies on complete collections of urine over a 24‐hour period but in many studies 24‐hour urine collections are not complete . The use of adequate criteria for assessing salt intake is important as otherwise inaccurate classification of an individual's salt consumption level will predispose to the null hypothesis or potentially U ‐shaped relationships if those who are noncompliant with 24‐hour urine collection are falsely classified as consuming low amounts of salt .…”
Section: Discussionmentioning
confidence: 99%
“…Accurately assessing individual salt intake requires several days of complete 24‐hour urine collections while our criteria only required a single 24‐hour period to assess salt intake. Accurate assessment of salt intake relies on complete collections of urine over a 24‐hour period but in many studies 24‐hour urine collections are not complete . The use of adequate criteria for assessing salt intake is important as otherwise inaccurate classification of an individual's salt consumption level will predispose to the null hypothesis or potentially U ‐shaped relationships if those who are noncompliant with 24‐hour urine collection are falsely classified as consuming low amounts of salt .…”
Section: Discussionmentioning
confidence: 99%
“…Forty‐five to fifty percent of respondents switched tertile of sodium intake when a single 24‐hour urine collection was used to estimate long‐term sodium intake vs sequential 24‐hour urine collections in a study from Amsterdam . The required number of 24‐hour urine collections to obtain a stable estimate of usual sodium intake is likely to differ with different dietary patterns, populations, and settings, and has been estimated to be at least 3 non‐consecutive days . Weaver et al found that ten 24‐hour urine collections were required to have a 75% reliability to estimate an individual's sodium intake when on a constant sodium diet and this number is likely higher when there is substantial day‐to‐day variation in sodium intake.…”
Section: ‐Hour Urine Collections To Assess Healthy Individual's Sodmentioning
confidence: 99%
“…32 The required number of 24-hour urine collections to obtain a stable estimate of usual sodium intake is likely to differ with different dietary patterns, populations, and settings, and has been estimated to be at least 3 non-consecutive days. 27,29,[31][32][33][34][35][36][37][38][39] Weaver et al 29 found that ten 24-hour urine collections were required to have a 75% reliability to estimate an individual's sodium intake when on a constant sodium diet and this number is likely higher when there is substantial day-to-day variation in sodium intake. The strength of the association between dietary sodium and health outcomes is highly influenced by the number of urine collections.…”
Section: -Hour Urine Collec Ti On S To a Ss E Ss He Althy Ind Ividmentioning
confidence: 99%
“…Incomplete urines are particularly of concern as non‐adherence even to placebo is associated with increased mortality as demonstrated in randomized controlled trials . Furthermore, due to large day‐to‐day variability of intake and excretion, a single 24‐hour urine sample is unlikely to give a valid estimate of usual intake, with at least 3 non‐consecutive days required . Additionally, sodium excretion was only measured at baseline; thus, estimates do not reflect any changes in intake over the 9‐year follow‐up period.…”
Section: Detailed Critical Appraisals Of Selected Studiesmentioning
confidence: 99%
“…41,42 Furthermore, due to large day-to-day variability of intake and excretion, a single 24-hour urine sample is unlikely to give a valid estimate of usual intake, with at least 3 non-consecutive days required. [43][44][45] Additionally, sodium excretion was only measured at baseline;…”
Section: Risk Of Biasmentioning
confidence: 99%